Nghiên cứu các yếu tố quyết định đến chính sách chi trả cổ tức bằng kĩ thuật hồi quy Fama - MacBeth: Bằng chứng thực nghiệm tại Việt Nam - Nguyễn Thị Ngọc Trang; Bùi Kim Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This paper examines the determinants of the dividend payout policy of non-financial firms listed on the Vietnamese stock market for the period between 2008 and 2015 using Fama and MacBeth’s (1973) methodology. Specifically, we analyze the effects of firm size, profitability, growth opportunities, risk, firm life-cycle, stock liquidity, financial leverage, and cash holdings on firms’ dividend payout policy. The results show that profitability, cash holdings, stock liquidity, and firm life-cycle play an important role in firms’ dividend policy. In addition, growth opportunities and financial leverage are determinants of dividend policy, whereas firm size and risk do not exert any effects on dividend decision of a firm.